BREAKING BARRIERS: A HISTORICAL STUDY OF WOMEN IN LEADERSHIP AND EDUCATION AT THE UNIVERSITY OF CALABAR, NIGERIA - Faith Nkechi Eborka; Jane Ikwunze (Malikussaleh Social and Political Reviews, 2025)
This study aims to discuss women's leadership in education, specifically at the University of Calabar, Nigeria (UNICAL). The role of women in education, previously considered a barrier, was later successfully overcome. This study examined educational institutions in Nigeria from 1975 to 2025. It highlights the barriers women have confronted over time, the milestones they have achieved, and the promise the future holds for female leadership and scholarship. UNICAL is a pioneer institution in Nigeria, which has succeeded in catalyzing gender dynamics and growth. It is little wonder, therefore, that it has produced notable females who have achieved tremendous feats in academia both nationally and internationally. Through a historical and qualitative lens, this research examines the impact of scholars such as Professor Florence Banku, the first female and 11th Vice Chancellor of the University of Calabar, Professor Aniebiet Inyang Ntui, the University Librarian; Professor Stella Ikhesor Ekpe, Dr. Bernadine Nse Ekpenyong, and a host of other notable females. The results of this study's investigation reveal the challenges women have faced in securing education, leadership roles, and influencing the overall academic culture at UNICAL. By documenting this narrative of excellence and analyzing the pattern of inclusion, this work will contribute to the broader discussion on gender equity in the Nigerian and African Higher Institutions. It offers recommendations for strengthening female academic participation in the years to come.